1964
DOI: 10.1021/jf60133a025
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Processing of Foods, Some Effects of Gamma Radiation on Keeping Quality of Apples

Abstract: Storage studies of applies treated with gamma radiation were conducted. The principal immediate effect was a softening by radiation dosages in excess of 10 kilorads, and a transient stimulation of respiratory oxygen consumption. Sauce was prepared from treated apples and evaluated as to quality. The principal effect of irradiation was a loss of "grain," which resulted in no significant change in acceptability or preference of the product. In storage, irradiated fruit softened at a much slower rate than did non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…As irradiation dose and storage time increase, firmness decreases. Numerous studies have reported that the softening of fruits induced by irradiation is associated with the decrease in total pectin content (Gunes et al, 2001;Massey and Smock, 1964). Gamma ray irradiation at doses above 400 Gy decreases the firmness of Fuji apples immediately after irradiation (Al-Bachir, 1999; Gunes et al, 2001;Mostafavi et al, 2012).…”
Section: Determination Of Firmnessmentioning
confidence: 99%
“…As irradiation dose and storage time increase, firmness decreases. Numerous studies have reported that the softening of fruits induced by irradiation is associated with the decrease in total pectin content (Gunes et al, 2001;Massey and Smock, 1964). Gamma ray irradiation at doses above 400 Gy decreases the firmness of Fuji apples immediately after irradiation (Al-Bachir, 1999; Gunes et al, 2001;Mostafavi et al, 2012).…”
Section: Determination Of Firmnessmentioning
confidence: 99%
“…Irradiation resulted in stimulation of respiration rate of apples, and generally tissues from more mature fruit were less sensitive to irradiation 8. 9 Romani et al 10 observed a divergent respiratory response of ‘Bartlett’ pears to irradiation dose, with higher levels of irradiation (6–10 kGy) resulting in a reduced respiratory activity compared with that of control fruits or those irradiated at lower levels (2–2.5 kGy).…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of WSP fractions to water-insoluble pectic acids during the onset of senescence results in decrease in WSP fractions. The low dose irradiation and low temperature storage have markedly delayed the activity of protopectinase and pectin methyl esterase enzymes responsible for degradation of protopectin and pectin (Massey et al, 1964). Loss in weight increased in all treatments including control during storage and the increase was significantly less under refrigerated conditions.…”
Section: Effect Of Gamma-irradiation On Firmness Tss Wsp Fractions mentioning
confidence: 95%
“…Irradiation and refrigeration are known to have a delaying effect on respiration and senescence, hence resulting in higher retention of TSS during storage. Irradiation at high doses lead to altered pore permeability, favouring respiration and senescence and thereby causing depletion in TSS (Massey et al, 1964;Wills et al, 1996;Chetan et al, 2006).…”
Section: Effect Of Gamma-irradiation On Firmness Tss Wsp Fractions mentioning
confidence: 99%